Journal of Neurodevelopmental Disorders - Vorstman, Jacob; Piven, Joseph; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Journal of Neurodevelopmental Disorders is an open access journal that integrates current, cutting-edge research across a number of disciplines, including neurobiology, genetics, cognitive neuroscience, psychiatry and psychology. The journal$1 (Bs primary focus is on the pathogenesis of neurodevelopmental disorders including autism, fragile X syndrome, tuberous sclerosis, Turner Syndrome, 22q Deletion Syndrome, Prader-Willi and Angelman Syndrome, Williams syndrome, lysosomal storage diseases, dyslexia, specific language impairment and fetal alcohol syndrome. With the discovery of specific genes underlying neurodevelopmental syndromes, the emergence of powerful tools for studying neural circuitry, and the development of new approaches for exploring molecular mechanisms, interdisciplinary research on the pathogenesis of neurodevelopmental disorders is now increasingly common. Journal of Neurodevelopmental Disorders provides a unique venue for researchers interested in comparing and contrasting mechanisms and characteristics related to the pathogenesis of the full range of neurodevelopmental disorders, sharpening our understanding of the etiology and relevant phenotypes of each condition.s
Keywords: Diseases$1 (BCauses and theories of causation.s; 9; Medical genetics; Nervous system$1 (BDiseases.s; Neuropsychology; Genetics; Pathogenesis; Neurology; Medical Genetics; Neurological Disorders; Neuropsychology; Genetics and Genomics